THE EFFECT OF AUDIT COMMITTEE, POLITICAL CONNECTION AND ISLAMIC CORPORATE GOVERNANCE ON TAX AGGRESSIVENESS AT ISLAMIC BANKS IN INDONESIA - Raudhatinur; Rahmiatul Aula; Venna Maulida Mustika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to examine the effect of audit committee, political connection and islamic corporate governance on tax aggressiveness at islamic banks in Indonesia. The population in this study is Bank General Sharia Which is registered with the Financial Services Authority. The sampling technique was carried out using purposive sampling technique. The companies used as samples in this study have the following criteria (1) Sharia banking companies registered with the Financial Services Authority from 2021-2023 (2) Islamic banking companies that provide complete financial reports and in accordance with the needs of research variables during the 2021-2023 research period. The research data uses secondary data, namely the Islamic Banking Financial Report in Indonesia with a research method using multiple linear regression analysis with SPSS 26. The result of this research showed that collectively and partially the audit committee, political connections and islamic corporate governance have simultaneous effect on tax aggressiveness at islamic banks in Indonesia